Analysis of Factors Affecting The Disclosure of Islamic Social Reporting (Empirical Studies on The Shariah Compliant Companies in The Sharia Securities List). - Peni Nugraheni; Ristina Wijayanti (Universitas Hayam Wuruk Perbanas, 2017)
The aim of this study is to obtain empirical evidence about factors that affect Islamic Social Reporting (ISR) in the Sharia compliant companies in Indonesia. The factors that used in this study are: company size, profitability, industry type, and ownership of Islamic securities. Measurement of Islamic Social Reporting is based on the Islamic Social Reporting Index developed by Othman (2010). The sampling method in this study is purposive sampling using companies that listed in Sharia Securities List on the year 2013. The analytical techniques was conducted by multiple regression method which showing that company size influences positively the Islamic Social Reporting (ISR) disclosure, meanwhile profitability, industry type, and Islamic securities ownership have no significant effect to the Islamic Social Reporting (ISR) disclosure in Indonesian Sharia Compliant companiesÂ Â